Faktor- faktor yang berhubungan dengan kejadian stunting pada 1000 hari pertama kehidupan - Yunani Yunani; Yuniastini Yuniastini (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Factors related to the occurrence of stunting in the first 1000 days of lifeBackground: Stunting is a problem that occurs in children under five and is a condition of failure to thrive in children under five which is a form of chronic malnutrition, repeated infections, and inadequate psychosocial stimulation, especially in the First 1000 Days of Life, from fetus to child. two years old. The percentage of stunting under five in Indonesia is 30.8% in 2018. In Lampung Province, Pesawaran Regency is the second-highest in Lampung, which is 33.5% in the very short category and 17.3% in the short category.Purpose: To find out the factors related to the occurrence of stunting in the first 1000 days of lifeMethod: The research method uses a descriptive method. The research sample is children in the first 1000 days of life in the Working Area of UPT Puskesmas Kota Dalam Pesawaran Regency in 2020. The number of samples is 266 consisting of 133 stunted children and 133 non-stunted children. Data collection uses a questionnaire.Results: Logistics Regression test found several variables related to stunting, namely the father's height (p=0.008) and the mother's knowledge (p=0.004). Meanwhile, the variables of maternal height, increased weight of pregnant women, birth weight, number of children, breastfeeding, maternal illness during pregnancy, income, distance to health facilities, were not associated with stunting.Conclusion: Descriptively, the data obtained are: The average father's height is 162.72 cm, the average height of the mother is 153.08 cm, the average weight gain during pregnancy is 8.49 kg, the average birth weight is 3114 g, the average knowledge value is 8.77 good category), the number of children is mostly 2 people, breastfeeding is mostly over 12 months, (59.4%), most of the mothers during pregnancy do not suffer from infectious diseases (worms, pulmonary TB, diarrhea), most of the family income is low (93.7%), most of the knowledge is sufficient.Suggestion: The management of the Public health center should improve health education for pre-pregnant women and provide to prevent stunting in their working area. As well as increasing community independence in nutritional adequacy.Keywords: Stunting; First 1000 days of life; Fetus; Weight of pregnancy; Number of children, Family income.Pendahuluan : Stunting merupakan masalah yang terjadi pada anak balita dan merupakan kondisi gagal tumbuh pada anak balita yang merupakan salah satu bentuk dari malnutrisi kronis, infeksi berulang, dan stimulasi psikososial yang tidak memadai terutama dalam 1000 Hari Pertama Kehidupan (HPK) yaitu sejak janin hingga anak berusia dua tahun. Persentase balita stunting di Indonesia 30.8 % pada tahun 2018. Di Propinsi Lampung, Kabupaten Pesawaran adalah nomor dua tertinggi di Lampung yakni sebesar 33,5% dalam kategori sangat pendek dan 17,3% dalam kategori pendek.Tujuan: Mengetahui factor yang berhubungan dengan kejadian Stunting pada balita di Wilayah kerja UPT Puskesmas Kota Dalam Tahun 2020.Metode: Penelitian menggunakan metode deskriptif, Sampel penelitian adalah anak 1000 hari pertama kehidupan di Wilayah Kerja UPT Puskesmas Kota Dalam Kab.Pesawaran Tahun 2020. Jumlah sampel 266 terdiri dari anak stunting 133 dan anak tidak stunting 133. Pengumpulan data menggunakan kuesioner.Hasil: Regresi Logistik menemukan beberapa variabel yang berhubungan dengan stunting yaitu tinggi badan ayah (p=0,000), usia ayah (p=0,000) usia ibu (p=0,009), pertambahan berat badan ibu hamil (p=0,029, jumlah anak (p =0,009) p=0,000), pendapatan keluarga (p=0,000).), weight gain of pregnant women (p=0.029, number of children (p=0.009) p=0.000), family income (p=0.000).Simpulan: Secara deskritif beberapa factor berkaitan erat dengan kejadian stunting dan beberapa factor dapat dicegah terjadinya stunting dengan peningkatan gizi dan nutrisi selama kehamilan.Saran: Manajemen Puskesmas supaya lebih peningkatan health education kepada ibu prahamil dan pendampingan untuk mencegah terjadinya stunting diwilayah kerjanya. Serta peningkatan kemandirian masyarakat dalam kecukupan nutrisi melalui pemanfaatan halaman rumah.